UNSUR KEBAHASAAN TEKS CERPEN DALAM KARANGAN SISWA KELAS VII SMP NEGERI 7 MUARO JAMBI - Ester Engjelia Sipahutar; Eddy Pahar Harahap; Deri Rachmad Pratama (P2M STKIP Siliwangi, 2025)
This study aims to describe the linguistic elements of short story texts in the compositions of class VII students of SMP Negeri 7 Muaro Jambi. The type of research in this study is qualitative. In this study, a descriptive method was used to determine and describe the linguistic elements of short story texts in the compositions of class VII students of SMP Negeri 7 Muaro Jambi. The data source in this study was the short story text of class VII D students of SMP Negeri 7 Muaro Jambi, observations of the linguistic elements of short story texts in student compositions. Data collection techniques used observation and documentation. The data validity test in this study used the triangulation technique. The theory in this study uses interactive data analysis of the Miles and Huberman model which consists of four stages. The first stage is data reduction, followed by data presentation, and in the third stage, drawing conclusions. The results of this study are that the short stories made by students as a whole do not contain one or two linguistic elements. In particular, students still have difficulty in using second person pronouns and inter-sentence conjunctions. The most common repetition elements are word repetition and phrase repetition. Most of the short stories made by students contain short story linguistic elements in the form of first and third person pronouns. And the short stories written by students often use intra-sentence conjunctions and only a few use inter-sentence conjunctions.